2014
DOI: 10.1038/nprot.2014.021
|View full text |Cite
|
Sign up to set email alerts
|

Surgical models for cardiac regeneration in neonatal mice

Abstract: Although amphibian and fish models of heart regeneration have existed for decades, a mammalian equivalent has long remained elusive. Our discovery of a brief postnatal window for heart regeneration in neonatal mice has led to the establishment of surgical models for cardiac regenerative studies in mammals for the first time. This protocol describes a 10-min surgical procedure to induce cardiac injury in 1-d-old neonatal mice. This allows for the analysis of cardiac regeneration after surgical amputation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
148
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(152 citation statements)
references
References 24 publications
3
148
0
1
Order By: Relevance
“…Consistent with previous reports, we demonstrate that neonatal mice have a remarkable ability to recover cardiac function, whereas adult mice have a significantly limited capacity (10)(11)(12)(13)(14). The precise macrophage characterization and lineage tracing studies performed herein show that the injured neonatal heart contains an embryonic-derived lineage of cardiac macrophages that promote cardiomyocyte proliferation and coronary angiogenesis, but produce minimal inflammation.…”
Section: Inhibition Of Monocyte Recruitment Preserves Embryonic-derivedsupporting
confidence: 76%
“…Consistent with previous reports, we demonstrate that neonatal mice have a remarkable ability to recover cardiac function, whereas adult mice have a significantly limited capacity (10)(11)(12)(13)(14). The precise macrophage characterization and lineage tracing studies performed herein show that the injured neonatal heart contains an embryonic-derived lineage of cardiac macrophages that promote cardiomyocyte proliferation and coronary angiogenesis, but produce minimal inflammation.…”
Section: Inhibition Of Monocyte Recruitment Preserves Embryonic-derivedsupporting
confidence: 76%
“…Recently, this regenerative capacity has been shown to exist in a mammalian system. It has been shown that newborn rodent hearts possess an endogenous regenerative capacity following multiple forms of injury, such as ventricular resection (Porrello et al, 2011;Mahmoud et al, 2014), cryoinjury (Jesty et al, 2012;Darehzereshki et al, 2015), coronary artery ligation (Haubner et al, 2012;Porrello et al, 2013;Mahmoud et al, 2014) and genetic cardiomyocyte ablation (Lavine et al, 2014). As observed in regenerating lower vertebrates, the replacement of lost cardiomyocytes in newborn rodents is dependent upon endogenous cardiomyocyte proliferation (Porrello et al, 2011(Porrello et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Neonatal mice were administered with a single pulse of tamoxifen at a dosage of 100 µg/g body weight at P1 and surgeries (apex resection and LCAL) were performed at P5 using a simple and convenient method as previously described (Fig. 6H) (Mahmoud et al, 2014). Histological analysis confirmed the success of these surgeries (Fig.…”
Section: Primary Contribution Of P53mentioning
confidence: 94%